2020
DOI: 10.1177/2054358120952904
|View full text |Cite
|
Sign up to set email alerts
|

Use of the FRAIL Questionnaire in Patients With End-Stage Kidney Disease

Abstract: Background: Frailty is a clinical phenotype of decreased physiologic reserve that is associated with increased morbidity and mortality. The most meaningful way to assess frailty in patients with end-stage kidney disease (ESKD) is unknown. Objective: To assess the prevalence of frailty in ESKD patients using the easy-to-administer FRAIL scale and, to determine its association with mortality, transplantation, and hospitalization. Design: A cohort study was used. Setting: The Ottawa Hospital, Ottawa, Ontario, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…In a small cohort of rural Chinese subjects undergoing chronic dialysis, the FRAIL scale demonstrated a good correlation with several clinical parameters, such as age, presence of comorbidities, and dialysis complications, better than the other six types of established self-report questionnaires (Strawbridge questionnaire, Edmonton Frail Scale, simple FRAIL scale, Groningen Frail Indicator, G8 questionnaire, and Tilburg Frail Indicator), although outcomes such as mortality or hospitalization were not assessed [ 16 ]. Additionally, another observational study [ 23 ] showed that frailty identified by the FRAIL scale was associated with an increased risk of hospitalization in adults treated with any dialysis modality (peritoneal dialysis, intermittent HD, or home HD). Also, the risk of death did not differ by frailty status, as observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small cohort of rural Chinese subjects undergoing chronic dialysis, the FRAIL scale demonstrated a good correlation with several clinical parameters, such as age, presence of comorbidities, and dialysis complications, better than the other six types of established self-report questionnaires (Strawbridge questionnaire, Edmonton Frail Scale, simple FRAIL scale, Groningen Frail Indicator, G8 questionnaire, and Tilburg Frail Indicator), although outcomes such as mortality or hospitalization were not assessed [ 16 ]. Additionally, another observational study [ 23 ] showed that frailty identified by the FRAIL scale was associated with an increased risk of hospitalization in adults treated with any dialysis modality (peritoneal dialysis, intermittent HD, or home HD). Also, the risk of death did not differ by frailty status, as observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The CFS has been extensively used to detect frailty and its association with diverse outcomes among dialysis patients [ 13 , 23 27 ]. The available studies with CFS are heterogeneous regarding study design, type of dialysis (peritoneal or HD), ethnicity, follow-up time, time of dialysis start, and patients’ age.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the generalizability of our study findings to current day patients is the continued pattern of hospitalization in patients identified as frail in studies involving more contemporary cohorts. 31 , 32 Despite attempts to include all patients who started chronic dialysis as an inpatient (in addition to the outpatient setting), it is possible that some patients may have died before being captured for electronic database entry and assigned a CFS score, introducing risk for selection bias. Finally, the CFS is subjective and different clinicians may grade severity differently or misclassify patients on the basis of limited availability.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported frailty predicted increased likelihood of in-centre HD modality choice (71,74,81). Eight studies reported frailty was associated with reduced likelihood of transplant referral and waitlisting, removal from waitlist or death on waitlist (42,55,(82)(83)(84)(85)(86)(87) while four studies reported an association with post-transplant complications (34,58,88,89).…”
Section: Frailty Outcomesmentioning
confidence: 99%